Innovation in Local Culture-Based Arabic Language Learning at Aishwa Nahla Islamic Boarding School, Palembang - Mukmin Mukmin; Nurul Hidayah; Irmansyah Irmansyah; Balyanan Furay Fisha; Salsa Vira Ningsih; Dea Marvina; Daud Elega (Universitas Muhammadiyah Sumatera Barat, 2026)
Arabic speaking instruction (maharah kalam) remains challenging due to the dominance of vocabulary memorization, grammatical mastery, and teachercentered learning with limited contextual relevance. This study examined Arabic language instruction at Aishwa Nahla Islamic Boarding School, analyzed the integration of Palembang local culture into maharah kalam learning, and evaluated its contribution to students’ Arabic competence. A mixed-methods approach with a sequential explanatory design. The study involved 26 eighthgrade students, while qualitative data also included one Arabic language teacher. Data were collected through observation, interviews, questionnaires, documentation, and pre-test–post-test assessments and analyzed using thematic analysis, paired-sample t-test, and N-Gain score. Findings revealed that integrating Palembang local culture fostered more communicative and contextualized learning. Students’ mean scores increased from 66.0 to 83.7 (p 0.05), with an N-Gain score of 52.39, indicating moderate effectiveness. The study suggests that local culture can serve as a meaningful pedagogical resource in Arabic-speaking instruction.